Virtual Forum Theater – a computer supported collaborative learning environment for underprivileged children - Cavallo, Alice C. Mello; Couch, Alva L. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2004)
This is an interdisciplinary research and a work in progress where we are trying to understand, investigate, document and critique how children’s learning of expressive arts, argumentation skills, and critical awareness can be augmented or transformed by the use of an on-line Forum Theater environment. The potential of this computer-based educational tool is to provide an open constructionist learning environment, or microworld, in which the learner can safely explore and express his imagination, creativity, language, aesthetics, participatory design, written skills, conflict resolution, role-playing, decision-making, and coordinated teamwork. We are studying the distinctions between learning in a regular drama environment using Theater of the Oppressed (TO) techniques, and an environment that blends drama, TO techniques and the Internet (Virtual Forum Theater learning environment).